TEACHING ENGLISH READING ABILITY FOR SECOND/FOREIGN LANGUAGE LEARNERS - Leffi Noviyenty (Indonesian Journal of Integrated English Language Teaching, 2017)
This article discusses the factors that affect the teaching of reading skills in English, for which the learners of English is the second language (L2) or as a foreign language (FL) and the alternative activities that may be done on the learning process in order to achieve the goals of effective reading learning. There are seven teaching principles that are needed to be considered and developed by reading teachers in the classes of English as second or foreign language. The seven principles of instruction should be applied in designing the reading class of English as a foreign language. The implementation of the seven principles will further optimize the students' reading ability in reading class of English as a foreign language for the students.